Nim's island / [Video recording] (Beverly Hillls, Calif.: 20th Century Fox Home Entertainment, 2008)
Nim Rusoe is a young girl who inhabits an isolated island with her scientist father and communicates, via e-mail, with the reclusive author of the novel she has been reading. Nim's existence mirrors that of her favorite literary character, Alex Rover, the world's greatest adventurer. But Alexandra, the author of the Rover books, leads a reclusive life in the big city. When Nim's father goes missing from the island, Nim gets Alexandra to come to her island. Now, the two must draw courage from their fictional hero, Alex Rover, and find strength in one another to conquer the island.